ВНЕДРЕНИЕ ИКТ В ПРОЦЕСС ОБУЧЕНИЯ РУССКОМУ ЯЗЫКУ - ЭФФЕКТИВНАЯ РЕАЛИЗАЦИЯ ПРИНЦИПОВ ИНДИВИДУАЛИЗАЦИИ, ДИФФЕРЕНЦИАЦИИ И САМОСТОЯТЕЛЬНОСТИ (Scientific journal of the Fergana State University, 2023)
Information technology as one of the integral components of the education system is not only open up the possibility of variability of educational activity, it’s individualization and differentiation, but also provide a new organizing the interaction of all subjects of study.